2009
DOI: 10.1103/physrevb.80.052403
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic depth profile of a modulation-dopedLa1xCaxMnO3exchange-biased system

Abstract: Recent magnetometry measurements in modulation-doped La 1−x Ca x MnO 3 suggested that a net magnetization extends from the ferromagnetic layers into the adjacent antiferromagnet layers. Here we test this hypothesis by polarized neutron reflectometry, which allows us to determine the depth resolved magnetization profile. From fits to the reflectivity data we find that the additional magnetization does not occur at the ferromagnetic/ antiferromagnetic interfaces, but rather in a thin region of the first antiferr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Intuitively, one would expect that the transition from FM metallic to paramagnetic insulating phases at the top LSMO interface would significantly reduce room temperature magnetization. To probe this, we use polarized neutron reflectometry (PNR), a scattering technique that allows us to measure the depth-resolved magnetic structure and is used to isolate individual magnetic layers in a thin-film heterostructure 16,[51][52][53][54] . Figure 6 shows the result of PNR measurements conducted at 298 K with a 1 T field applied along the substrate [100] direction.…”
Section: Resultsmentioning
confidence: 99%
“…Intuitively, one would expect that the transition from FM metallic to paramagnetic insulating phases at the top LSMO interface would significantly reduce room temperature magnetization. To probe this, we use polarized neutron reflectometry (PNR), a scattering technique that allows us to measure the depth-resolved magnetic structure and is used to isolate individual magnetic layers in a thin-film heterostructure 16,[51][52][53][54] . Figure 6 shows the result of PNR measurements conducted at 298 K with a 1 T field applied along the substrate [100] direction.…”
Section: Resultsmentioning
confidence: 99%
“…For the FM LSMO layer, deposited immediately after the o-YMO one, the parameters were 10 Hz repetition rate and 0.35 (0.38) mbar oxygen pressure, 8 (30) nm thickness and at the same laser fluency and substrate temperature, for sample A (B). In order to corroborate the contribution of the FM layer in the M E -shift we have decreased further the oxygen concentration to deposit the LSMO film in sample C (oxygen pressure 0.10 mbar) with a larger thickness of 225 nm decreasing in this way its coercivity.…”
Section: Sample Preparation Details and X-ray Characterizationmentioning
confidence: 99%
“…We remark that unexpected phenomena can occur at oxide interfaces. A recent study, for example, found an excess magnetization produced at the interface between STO and an AFM La 1/3 Ca 2/3 MnO 3 layer, 30 which origin remains unclear. In our case the large m shift valuesactually a giant M E effect -indicate that a large contribution should come from the FM layer.…”
Section: A Single Ymno3 Layersmentioning
confidence: 99%
“…The effects at the interface between the FM and AF layers were found among the main reasons for such a behavior, meaning that at the interfaces-in addition to the type of antiferromagnetic material where research has to focus-the F/AF multilayers show a collective contribution due to the high number of interfaces. Polarized neutron reflectometry measurements on F-LCMO/AF-LCMO superlattices, which permitted determining the depth-resolved magnetization profile, showed that additional magnetization does not occur at the ferromagnetic/antiferromagnetic interfaces, but rather in a region of the first antiferromagnetic layer adjacent to the interface with the substrate [5]. Therefore, the magnetization structure in these superlattices, possibly influenced by the complex electronic and magnetic interactions both at the F/AF interfaces and bulk, is more complex than that expected from nominal chemical doping profile.…”
Section: Introductionmentioning
confidence: 99%